« Indiens ou Noirs, libres ou esclaves » : travail et métissage en Amazonie portugaise (xviie et xviiie siècles) - Rafael Chambouleyron; Karl Heinz Arenz (Caravelle)
Historiography considered the Portuguese colonial Amazon region as being a “land of Indians”. Scholars argued that African slavery was economically just not possible, due to the settlers’ poverty, and especially the region’s geographical isolation, which hindered the connection of this province with the main trade circuits of the Portuguese empire. However, besides the many references to Indians in the registers, colonial documentation frequently mentions Africans and Mestizos. Analysing colonial sources dealing with and produced in Portuguese Amazonia, and based on the specific economic and social dynamics of this region, this paper examines the construction of an ethnically diversified world of labour, where Indians, Africans and Mestizos were interacting in an inextricable way.